The evolution of a jet ejection of the ultraluminous X-ray source Holmberg II X-1 - Cseh, D.; Miller-Jones, James; Jonker, P.; Grisé, F.; Paragi, Z.; Corbel, S.; Falcke, H.; Frey, S.; Kaaret, P.; Körding, E. (Oxford University Press, 2015)
We present quasi-simultaneous, multi-epoch radio and X-ray measurements of Holmberg II X-1 using the European VLBI Network (EVN), the Karl G. Jansky Very Large Array (VLA), and the Chandra and Swift X-ray telescopes. The X-ray data show apparently hard spectra with steady X-ray luminosities four months apart from each other. In the high-resolution EVN radio observations, we have detected an extended milliarcsecond scale source with unboosted radio emission. The source emits non-thermal, likely optically thin synchrotron emission, and its morphology is consistent with a jet ejection. The 9-GHz VLA data show an arcsecond-scale triple structure of Holmberg II X-1 similar to that seen at lower frequencies. However, we find that the central ejection has faded by at least a factor of 7.3 over 1.5 yr. We estimate the dynamical age of the ejection to be higher than 2.1 yr. We show that such a rapid cooling can be explained with simple adiabatic expansion losses. These properties of Holmberg II X-1 imply that ULX radio bubbles may be inflated by ejecta instead of self-absorbed compact jets.